Benthic faunal assemblages in seagrass meadows in Albany, Western Australia - Rifai, Husen (AQUATIC SCIENCE & MANAGEMENT, 2019)
Title (Bahasa Indonesia): Kumpulan fauna bentik di hamparan lamun di Albany, Australia Barat In order to compare benthic fauna assemblages in four locations of seagrass beds in Albany (Princess Royal Harbour, Oyster Harbour, Two People Bay and Frenchman Bay), a research had beenconducted between 18 and 21 April 2017. There were two aims of this study. First, to investigate six sites within four locations with various degree of anthropogenic impact in order to understand the faunal richness and abundance in those locations. Second, to measure and record the environmental factors which are assumed to be important regulators of the observed patterns between the sites. The result showed that the highest faunal abundance (227 Faunal) was found at Frenchman Bay, a less anthropogenically impacted area, while the lowest abundance (26 Faunal) was at Oyster Harbour-Emu Point which was an anthropogenically affected site. However, in terms of faunal diversity, there was no significant difference among all sites. The environmental factor which had significant relationship with the difference in benthic faunal assemblages at each site was found to be coarse sand.Satu kegiatan penelitian pada tanggal 18 hingga 21 April 2017 telah dilakukan untuk membandingkan kumpulan fauna bentik di empat lokasi padang lamun di Albany (Pelabuhan Princess Royal, Pelabuhan Oyster, Teluk Two People, dan Teluk Frenchman). Penelitian inimempunyai dua tujuan, yaitu: 1) menyelidiki enam titik penelitian yang beradadalam empat lokasi dengan berbagai tingkat dampak antropogenik untuk memahami kekayaan dan kelimpahan fauna di lokasi tersebut; dan 2) mengukur dan mencatat faktor-faktor lingkungan yang dianggap berperan sebagai pengaturdari pola yang diamati pada semua lokasi. Hasil penelitian menunjukkan,bahwa kelimpahan fauna tertinggi (227 fauna) ditemukan di Teluk Frenchmanyang merupakandaerah yang kurang terdampak gangguan antropogenik;sedangkan kelimpahan terendah (26 individu) ditemukandi Oyster Harbour-Emu Point yang merupakan lokasi yang terpengaruh secaraantropogenik. Namun, dalam hal keanekaragaman fauna, tidak ada perbedaan yang signifikan di antarasemua lokasi. Faktor lingkungan yang memiliki hubungan signifikan dengan perbedaan kumpulan fauna bentik di masing-masing lokasi ialah pasir kasar.